2015
DOI: 10.1007/s00402-015-2239-1
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of rotator cuff tears: a systematic review

Abstract: The development of symptoms and anatomical deterioration are often directly correlated. Spontaneous recovery to normal levels of function has been successfully achieved, and standardised non-operative treatment programmes are an effective alternative to surgery for many patients. Follow-up is necessary to avoid irreparable stage. However, surgery is still favoured by young active people and highly professional persons who need to get fit in a short period of time. Further research is still necessary. The AMQPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 18 publications
0
23
0
2
Order By: Relevance
“…Although this is an auto-controlled study, which is considered to be a weak design, there is evidence that the natural history of symptomatic rotator cuff injuries indicates that they mostly tend to progression and not to spontaneous resolution [222324]; hence, the outcome of implementation of the TR program is unlikely to be due to a placebo effect or the natural history of disease. It is noteworthy that the CM scale includes quantitative assessments of mobility and strength, and the study showed significant improvement in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is an auto-controlled study, which is considered to be a weak design, there is evidence that the natural history of symptomatic rotator cuff injuries indicates that they mostly tend to progression and not to spontaneous resolution [222324]; hence, the outcome of implementation of the TR program is unlikely to be due to a placebo effect or the natural history of disease. It is noteworthy that the CM scale includes quantitative assessments of mobility and strength, and the study showed significant improvement in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…10) On one hand, Mall et al 5) reported that across a 2-year or longer follow-up fullthickness rotator cuff tears increased by 5 mm in 18% of patients A B and partial tears progressed into full-thickness tears in 40% of patients (n=195). On the other hand, Fucentese et al 11) reported that the increase in tear size observed on magnetic resonance arthrograms after a 3.5-year follow-up was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the accuracy of MRI in diagnosing full-thickness rotator cuff tears is greater than 95%. [9][10][11][12][13][14] In this study, we analyzed MRI findings of patients who were initially hospitalized for shoulder pain, which was diagnosed as a rotator cuff tear, were treated conservatively, but were later re-hospitalized for recalcitrant tears that were neglected without appropriate treatment. We investigated the natural history of the rotator cuff tears in terms of the change in cuff tear size, as measured on patients' MRI scans, and of clinical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…32 Other studies have found that it is unlikely that outcomes will worsen if a tear is left for 3 months post-trauma. [33][34][35] Most people who fail non-surgical treatment are likely to request surgery within the first 12 weeks. Beyond 12 weeks of non-surgical management there appears to be no further uptake in people requesting surgery.…”
Section: Non-surgical Management Of Rotator Cuff Tearsmentioning
confidence: 99%